Motivational Differences in Choosing to Study Languages at University : A comparison between students majoring in English, Finnish, and Other Additional Languages - Valonen, Tiia (My University, 2024)
This thesis aims to compare the motivational differences in choosing to study languages at university between students of English, Finnish, and languages other than English. The study focuses on the students’ initial interest in studying language at university, examining both general interest in languages and the desire to learn more of the major subject language. In addition, the reasons behind students’ decisions to study languages at university were analysed, along with their prospective career aspirations. This study utilised questionnaire data from 672 first-year language majors. The data were analysed both quantitatively and qualitatively. Initial interest in languages was analysed using descriptive statistics. Differences in interest between the groups were measured using the Kruskal-Wallis Test. Lastly, students’ reasons for choosing to study languages and prospective career aspirations were examined using data-driven content analysis. The study showed that first-year language majors are highly interested in studying languages, with students studying languages other than English being the most motivated. Students were more interested in learning more of their major subject language compared to general interest in languages. Students had multiple reasons for choosing to study languages at university. These reasons were interest in the major subject language, professional goals, perceived language skills, the desire to learn more, general interest in languages, cultural interest, usefulness of the language, indecision and lack of direction, and the desire to study at a university. In addition, students had multiple professional goals. These goals were education-related fields, translation, specialist roles, international aspirations, media and communications, research, political and administrative professions, professions related to literature, creative professions, technology-related fields, and other ambitions. A large majority of the students also expressed uncertainty regarding their prospective profession.
Keywords: L2 motivation, motivational factors, university students, career aspirations